Is Reading Instruction Evidence-Based? Analyzing Teaching Practices Using T-Patterns - Suárez, Natalia; Sánchez, Carmen R.; Jiménez, Juan E.; Anguera, M. Teresa (Frontiers in Psychology, 2018)
The main goal of this study was to analyze whether primary teachers use evidence-based reading instruction for primary-grade readers. The study sample consisted of six teachers whose teaching was recorded. The observation instrument used was developed ad hoc for this study. The recording instrument used was Match Vision Studio. The data analysis was performed using SAS, GT version 2.0 E and THEME. The results indicated that the teaching practices used most frequently and for the longest duration were: feedback (i.e., correcting the student when reading); fluency (i.e., individual and group reading, both out loud and silently, with and without intonation); literal or inference comprehension exercises (i.e., summarizing, asking questions); and use of educational resources (i.e., stories, songs, poems). Later, we conducted analyses of T-Patterns that showed the sequence of instruction in detail. We can conclude that less than 50% of the teaching practices used by the majority of teachers were based on the recommendations of the National Reading Panel (NRP). Only one teacher followed best practices. The same was the case for instructional time spent on the five essential components of reading, with the exception of teacher E., who dedicated 70.31% of class time implementing best practices. Teaching practices (i.e., learners’ activities) designed and implemented to exercise and master alphabetic knowledge and phonological awareness skills were used less frequently in the classroom.